Employee Engagement as a Condition for Employee Well-being - Kinowska, Hanna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2021)
Objective: The purpose of this article is to analyse the relationship between employee well-being and three aspects of engagement: vigour, dedication to work and absorption.Research Design & Methods: The research hypotheses are derived from the subject literature. Exploration of the relationships between the constructs was based on a CAWI survey conducted in January 2021 on a sample of 1,000 working Poles. The relationships were examined using Rho Spearman correlation and multiple regression analyses.Findings: Energy, pleasure, enthusiasm for work, a sense of pride and meaning in one's tasks all have a positive impact on employee well-being. For Poles, being absorbed in work and doing it with passion has no bearing on well-being.Implications / Recommendations: The survey results confirmed the existence of a relationship between employee engagement and the well-being of working Poles. Employee well-being is positively affected by vigour and dedication to one’s work. Work absorption was not found to have an effect on well‑being.Contribution: The study contributes to the knowledge base on the impact of engagement factors on employee well-being. The results suggest that employee well-being can be explained with comprehensive models.